1989
DOI: 10.1111/j.1365-2958.1989.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of mycobacteria by amplification of mycobacterial DNA

Abstract: A 383bp segment of the gene coding for the 65kD mycobacterial antigens from Mycobacterium tuberculosis, Mycobacterium bovis, Mycobacterium avium, Mycobacterium paratuberculosis, and Mycobacterium fortuitum was amplified using Taq polymerase and synthetic oligonucleotide primers and the amplified DNAs from four of these species were compared by nucleotide sequencing. Although the gene segments from these species showed considerable similarity, oligonucleotide probes which could distinguish M. tuberculosis/M. bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
4

Year Published

1992
1992
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(147 citation statements)
references
References 24 publications
1
142
0
4
Order By: Relevance
“…The 383 bp sequence of the 65 KDa antigen of Mycobacterium tuberculosis was amplified 2,5 . After agarose gel electrophoresis, amplification products were transferred to nylon membrane by Southern blotting technique and hybridized with a specific M. tuberculosis probe 1 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The 383 bp sequence of the 65 KDa antigen of Mycobacterium tuberculosis was amplified 2,5 . After agarose gel electrophoresis, amplification products were transferred to nylon membrane by Southern blotting technique and hybridized with a specific M. tuberculosis probe 1 3 .…”
Section: Methodsmentioning
confidence: 99%
“…All positive colonies were subcultured and identified (according to colony morphology, growth temperature and pigment production). For further identification we performed biochemical tests for nitrate reduction, catalase, Tween 80 hydrolysis, amidase, aryl sulphatase, pyrazinamidase and urease (Kent and Kubica, 1985), and polymerase chain reaction (PCR) (Hance et al, 1989;Kunze et al, 1992). Isolates identified as members of the M. avium complex were also serotyped.…”
Section: Identification Of the Isolatesmentioning
confidence: 99%
“…Rapid and sensitive tools for the diagnosis of tuberculosis have been developed recently. In this context, the amplification of specific nucleic acids by polymerase chain reaction (PCR) provides a means for both increasing the sensitivity of detection and reducing the time required to diagnose pulmonary tuberculosis [5,61. Several studies have reported the success of PCR for the detection of M. tuberculosis DNA in clinical specimens such as sputum [7-lo].…”
Section: Introductionmentioning
confidence: 99%